Impacto da Transição Social Precoce na Saúde Mental de Crianças com Disforia de Género - Matilde Marinheira Dias Sampaio Monteiro (2021)
Early social transition is an increasingly popular approach to prepubertal children with Gender Dysphoria. Nonetheless, its possible benefits or disadvantages remain unknown, especially the ones regarding the child's psychological well-being. This review aims to display the existing scientific evidence concerning the impact of social transition on the mental health of these children. A research for articles on mental health and early social transition in Child Gender Dysphoria was conducted on the MEDLINE database, from which five studies were selected. In four studies, socially transitioned children had equivalent psychopathology levels to the populational average. Two studies inferred that children's psychological well-being was not correlated with the status of social transition or the degree of family acceptance, but with the quality of the relationship with their peers. This review shows that pre-pubertal transgender children whose gender identity is affirmed and supported might have good psychological functioning. However, it is not yet possible to conclude the direct effect of social gender transition on children's mental health.